(3GdYedjGJ GdeUQajI hGdShb GdeGdjI(B: :s (3GdfXGe GdbGfhfj ddfXGe GdeUQaj aj dHfGf eY edMb TGed HGdbhGfjf hGdGMJeGdGJ GdLRA GdGhd (B/s - (3GdfGTa, CfWhGfs; (3GdgfOj, Ndjd s ((3WQGHdS(B: s (3GdeDSSI GdMOjKI ddcJGH(B, s, 1998)
(3GdJWhQ GdJGQjNj hGdJTQjYj ddfXGe GdfbOj aj dHfGf(B-(3GdJWhQ GdJGQjNj hGdJTQjYj ddfXGe GdeUQaj aj dHfGf(B-(3eQGMd GdEUdGM GdeUQaj(B-(3eUQa dHfGf(B-(3GdeUGQa GdJLQGjI(B-(3bhGYO EfSGA hEOGQI GZdeUGQa GdJLQGjI aj dHfGf(B-(3GdhOGFY GdeUQajI(B-(3GdJSdjaGJ GdeUQajI(B-(3GdSQjI GdeUQajI(B-(3JHjjV GdCehGd(B-(3GdQbGHI Ydi GdeUGQa(B-(3GdLQGFe GdLRGFjI aj GdbGfhf GdfbO hGdJSdja hGdSQjI GdeUQajI(B-(3GdfXGe GdbGfhfj ddTjc aj dHfGf(B-(3GdQGSeGd GdeUQaj(B-(3HWGbGJ GdGFJeGf(B-(3GdeDSSI GdhWfjI dVeGf GdhOGFY(B-(3GdOeL GdeUQaj(B-(3ELJgGOGJ aj ehVhY GdeUGQa(B-(3GdbhGfjjf hGdJYGeje GdeJYdbI HGdYed GdeUQaj aj dHfGf(B.s
Keywords: (3GdYedjGJ GdeUQajIs